HUBUNGAN EXPLOSIVE POWER OTOT TUNGKAI DAN KOORDINASI MATA-TANGAN DENGAN HASIL MEDIUM SHOOT TIM BASKET PUTRA SMAN 1 RENGAT - Winda Wardani; Saripin '; Kristi Agust (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: the problem in this research was less ability on medium shoot result in basketball men’s team senior high school 1 Rengat. It was suppose cause of less explosive power of leg muscle and eyes – hand coordination when did medium shoot. The aim of this research was to know about correlation on explosive power of leg muscle and eyes – hand coordination with medium shoot ability. Type of this research was correlation with aim to know extant connection between free variable and baound variable. After that, normality data test with Liliefors test with significant planed α = 0.05, and find the normality test of variable’s value was X1, L0maks (0,0983) < Ltable (0,242), normality test of variable X2, L0maks (0,1185) < Ltable (0,242), normality test of variable Y, L0maks (0,1545) < Ltable (0,242) with other word was normally of data distribution. Then continued to found r used product moment correlation analysis and double correlation, if rresult > rtable so it was have significant correlation. The result of this research showed: it was significant correlation between explosive power of leg muscle and eyes – hand coordination with medium shoot result, Rresult (0,7764) > Rtable (0,602). So, Ho refused and Ha accepted. The conclusion was have significant correlation between explosive power of leg muscle and eyes – hand coordination with medium shoot result at male basketball team of SMAN 1 Rengat.Keywords: explosive power of leg muscle, eyes – hand coordination, medium shoot.